Circadian Mechanisms: Cardiac Ion Channel Remodeling and Arrhythmias - Bernardi, Joyce; Aromolaran, Kelly A.; Zhu, Hua; Aromolaran, Ademuyiwa S. (Frontiers in Physiology, 2021)
Abstract Circadian rhythm is involved in many physiological and pathological processes in different tissues, including the heart. Several adverse cardiovascular events have different temporal presentation, highlighting a significant contribution of circadian mechanisms in pathophysiology of cardiac electrical function. In this review we focus on the current knowledge of circadian modulation of autonomic nervous system and cardiac ion channels, with particular attention to supraventricular and ventricular arrhythmias. We further consider the contribution of circadian mechanisms in metabolic disorders, such as obesity and diabetes, disease mechanisms that increase vulnerability to fatal arrhythmias and ultimately the transition to sudden cardiac death. Our hope is that if we are able to fully understand the temporal modulation of cellular signaling system and its effect on cardiac electrical function, we may be able to better provide relevant mechanism-based insights that will help to improve the quality of life and longevity of patients with heart diseases.